KKN Tematik : Bersama Memajukan Desa Memanfaatkan Potensi UMKM untuk Kesejahteraan Masyarakat Kelurahan Pematang Gubernur - Listeriani, Eva; Iskandar, Ghovinda Kumala; Wijaya, Gino; Bintang, M Ilham; Syahputra, M Iqbal; Putra, Dwingki Marta; Suwarni, Suwarni; Susanti, Neri; Soleh, Ahmad; Asnawati, Asnawati; Martiani, Martiani (Universitas Dehasen Bengkulu, 2025)
This Thematic KKN was carried out with the aim of building synergy between students, the Pematang Gubenur Village community, and various related parties to jointly advance the village through the development of MSMEs. Through training, mentoring, and socialisation activities, it is expected to increase the knowledge and skills of MSME actors in managing their businesses. In addition, this activity also aims to build a wider marketing network for local MSME products so as to increase the income of the village community. With the resulting product, namely the manufacture of garbage cans for the village.